Design and Implementation of Controller for Boost DC-DC Converter Using PI-LPF Based on Small Signal Model - Kasbi, Slamet; Rijanto, Estiko; Abd Ghani, Rasli bin (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
Boost DC-DC converters are used in many renewable energy sources including photovoltaic and fuel cell. They are also used in Uninterrupted Power Supply, inverters, electric vehicles and robots. In this paper a boost converter was built and its controller was developed using proportional integral (PI) action for current loop and low pass filter (LPF) for voltage loop. The controller was derived analytically based on small signal model. Experiment results show that the boost controller functions well in regulating the output voltage under a variation of load. During the start up without any load it can elevate input voltage from 119.6V to output voltage of 241.6V. The developed controller can regulate the output voltage smoothly under load variation from no load to sudden load of 352W. When a large sudden load change happens from 0W to 1042W the output voltage experiences small drop before it is recovered to 241.6V. It can be concluded that the developed control system satisfies the design specification.